A decentralized control method for eliminating voltage asymmetry in low-voltage electric networks with integrated solar panels - Ilkhombek Kh. Kholiddinov; Mukhlisakhon M. Begmatova (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: modern electric power systems based on a centralized management architecture demonstrate vulnerability in emergency and non-standard situations. Such events indicate the need to move to a new management model focused on decentralized and sustainable solutions, especially in the context of the active integration of distributed photovoltaic (PV) sources into low-voltage networks. In the context of the energy transition in Uzbekistan, accompanied by digitalization, the development of "green" generation and the introduction of Smart Grid elements, the task of ensuring voltage symmetry and reliability of power supply with a high proportion of renewable energy sources is of particular relevance. One of the most effective approaches to solving these problems is decentralized management based on local intelligent controllers, which ensures the autonomy, adaptability and stability of electrical networks. Aim: to substantiate the effectiveness of using a decentralized control system to reduce voltage asymmetry and increase the stability of low-voltage electric networks with integrated solar panels, using local measurements, IoT infrastructure and phase redistribution. Methods: comparative analysis of Smart Grid control architectures, assessment of the influence of single-phase generation on voltage symmetry, as well as structural modeling of cascade and general decentralized control circuits were used. Results: the proposed architecture of decentralized management in PV networks provides high adaptability, ease of implementation and reduces the need for a large-scale communication infrastructure.